2016
DOI: 10.1002/1873-3468.12310
|View full text |Cite
|
Sign up to set email alerts
|

Reduced levels of Dusp3/Vhr phosphatase impair normal spindle bipolarity in an Erk1/2 activity‐dependent manner

Abstract: Dual specificity phosphatase-3 (Dusp3/Vhr) regulates cell cycle progression by counteracting the effects of mitogen-activated protein kinases (Mapk) Erk1/2 and Jnk. Despite the known upregulation of Dusp3 at M phase in mammalian cells, its mitotic functions are poorly characterized. Here, we report that loss of Dusp3 by RNAi leads to the formation of multipolar spindles in human mitotic cancer cells in an Erk1/2-dependent manner. In the phosphatase-silenced cells, the normal bipolar spindle structure was resto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 41 publications
(60 reference statements)
0
11
0
1
Order By: Relevance
“…In terms of MAPK signaling, with MAPKs the best characterized substrates of VHR, over-activating ERK1/2 induced multipolar spindles and aneuploidy in cells, while inhibiting ERK1/2 did not cause defects during chromosomal events such as the spindle assembly checkpoint (SAC) and mitotic exit 49 . The role of this phosphatase in the formation of multipolar spindles in cancer cells was recently investigated 50 . In early mitotic mammalian cells, both VHR and ERK1/2 localized to the spindle apparatus 17 , 51 , and transient VHR inhibition promoted the formation of multipolar spindles in human mitotic cells 50 .…”
Section: Biological Functions Of Vhr/dusp3 and Its Association With Hmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of MAPK signaling, with MAPKs the best characterized substrates of VHR, over-activating ERK1/2 induced multipolar spindles and aneuploidy in cells, while inhibiting ERK1/2 did not cause defects during chromosomal events such as the spindle assembly checkpoint (SAC) and mitotic exit 49 . The role of this phosphatase in the formation of multipolar spindles in cancer cells was recently investigated 50 . In early mitotic mammalian cells, both VHR and ERK1/2 localized to the spindle apparatus 17 , 51 , and transient VHR inhibition promoted the formation of multipolar spindles in human mitotic cells 50 .…”
Section: Biological Functions Of Vhr/dusp3 and Its Association With Hmentioning
confidence: 99%
“…The role of this phosphatase in the formation of multipolar spindles in cancer cells was recently investigated 50 . In early mitotic mammalian cells, both VHR and ERK1/2 localized to the spindle apparatus 17 , 51 , and transient VHR inhibition promoted the formation of multipolar spindles in human mitotic cells 50 . These studies also demonstrated that depleting ERK1/2 activity but not JNK restored the multipolarity induced by a lack of VHR and that overexpressing VHR reduced ERK1/2 phosphorylation by reversing multipolar spindles.…”
Section: Biological Functions Of Vhr/dusp3 and Its Association With Hmentioning
confidence: 99%
“…The cancer-related DUSP4 overexpression blocks ERK1/2 signalling, and this leads to increased cell proliferation in colorectal cells 45. Expression of DUSP3 is needed during intensive cell proliferation to inhibit the active MAPK signal, and blocking DUSP3 by compounds leads to cell cycle arrest 46,47. Therefore, DUSP3 could be a potential drug target in colon cancer, similarly as it was proven in cervical cancer, where targeting DUSP3 by small molecules led to decreased proliferation 48.…”
Section: Resultsmentioning
confidence: 94%
“…Interestingly, DUSP4 alone can still limit the ERK1/2 over activation leading to cancer stem cell formation and epithelial mesenchymal transition (EMT) instead of cell-cycle arrest 50. The inhibition of DUSP4 could prevent the EMT in breast cancer,50 as well as causing cell cycle arrest, similarly as the inhibition of DUSP3 in colorectal cancer 46. Therefore, DUSP4 inhibitors (such as the CHEMBL 2146956 compound, which inhibits DUSP4 with an IC50 of 2.29 μm) are under intensive experimental investigations.…”
Section: Resultsmentioning
confidence: 99%
“…DUSP3 is a dual activity phosphatase that regulates signaling pathways by dephosphorylating target tyrosine and/or serine/threonine residues [59]. While DUSP3 has been shown to specifically target ERK1/2 and JNK MAP kinase (MAPK) pathways in multiple cancers [58,60,55,56], its role in melanoma is unknown. To investigate the specific kinase pathway(s) regulated by DUSP3 in A375 cells, we assessed phosphorylation of various MAPK pathway members using a MAPK array upon DUSP3 knockdown ( Fig.…”
Section: Dusp3 Is An Mir-211 Target In A375 Cells Where It Promotes Cmentioning
confidence: 99%